Stories women tell five rural women lived experiences of survival and typhoons (2012)
This paper is an initial exploration of five rural women's interpretations of their lived experiences of daily survival and typhoons. Using feminist standpoint epistemology that builds knowledge from women's experiences, the paper privileges the concrete experiences of the five rural women and their perspectives in viewing rural poverty, women's vulnerabilities in times of typhoons, their difficulties in surmounting the after-effects of typhoons, and their strategies in rebuilding their lives.
Keywords: Irosin (Sorsogon) -- Environmental conditions; Poor women -- Irosin (Sorsogon); Rural women -- Irosin (Sorsogon); Women -- Research